Fundamental energy limits in the physics of nanomagnetic binary switches. (July 2015) - Madami, M.; Chiuchiù, D.; Carlotti, G.; Gammaitoni, L.
Abstract: Binary switches are the basic element of modern digital computers. In this paper we consider a magnetic binary switch consisting of a nanodot constituted by a single cylindrical ferromagnetic element with two stable energy minima and perform virtual experiments using numerical simulations based on the micromagnetic approach. The fundamental limits in minimum energy dissipation are discussed presenting two, popularly adopted, switching procedures. We show that the zero-power limit is only attainable with one of the two protocols, which does not involve any irreversible entropy increase. Moreover, the influence of the energy barrier height in the presence of fluctuations and the role of bit-flip errors is quantitatively analyzed. Graphical abstract: Highlights: We investigate the minimum energy limits for the switch operation of a nanomagnet. We propose two different switching protocols. Dynamic and entropic reversibility are required for a zero-power switching. A proper choice of the energy barrier height is needed for efficient switching.